Humanitarian Action & Coordination – Humanitarian Technology : Balancing Protection with Flexibility - Searle, Martin (2017)
New technologies present regulatory questions. This is no less true of technologies deployed in humanitarian settings. But disaster contexts raise unique regulatory challenges. Addressing them requires balancing competing imperatives while maintaining the flexibility that is crucial to emergency response.